Effect Of Spot Welding Processing Parameters On Ferrous And Non Ferrous Metal - Abd Halim, Mohd Fahmi Hafiz (Universiti Sains Malaysia, 2018)
Resistance Spot Welding (RSW) is the joining metal process that has been widely used in industry nowadays especially in aerospace and automotive industry. RSW method is focusing on the joining of sheet metal combination because of its limitation to the certain thickness only. There has many research has been done on discussing about the effect of welding parameters towards the properties and behaviour of spot welded joint. However, this project is focusing on resistance spot welding (RSW) parameters towards the tensile strength of the spot welded joint. The selected welding process parameters involved are squeeze time, of 50ms and 100ms, welding pressure, of 0.37kN and 0.38kN and also welding current of 4kA and 7kA. Experiments were conducted by joining the similar combination of materials for copper, aluminium and galvanized iron and dissimilar materials combination for copper and galvanized iron. The reliability of the data expressed in form of Z score value for each set combination. They are calculated and plotted in the bell shaped graph to make sure all the Z score value is placed between range of -2 to 2. There are some few problems in the RSW method such as burn marks on the spot welded joint and surface damage due to over pressure during RSW process.